Fresno's Historic Van Ness Avenue Entrance Sign - Watkins, Howard::::::::: (1984)
"FRESNO The Best Little City in the U.S.A. Van Ness Ave. Entrance" sign south of downtown area Adam Watkins standing under sign; Chick's Wheel Service shop in background